Learning atmospheres: Re-imagining management education through the dérive. Issue 5 (November 2020) - Michels, Christoph; Hindley, Clare; Knowles, Deborah; Ruth, Damian
This article responds to the recent calls for rethinking management education, particularly to those that emphasize space, affect and atmosphere, and makes the case for the practice of dérive as a way of infusing management education with experiential, experimental and reflexive learning processes. The authors draw on ideas and practices of the art movement Situationist International who proposed the dérive, informed by the concept of psychogeography as a way of exploring and reimagining the atmospheres of everyday life. The paper is illustrated by the authors' teaching experiences in this area (or space as one might say). The authors argue that the dérive in management education may foster future managers' imaginative skills and inspire an imaginative self-reflection of the business school and its spatial organization. The paper concludes that in re-enacting their experience of educational space, participants may learn about, reflect on, and develop their affective capacities for becoming part of organizational processes, both as students of the business school and as future managers.